Distribution of HCV genotypes among patients attending south Indian tertiary care centre - Masood Ahmed Tahashildar; Morubagal Raghavendra Rao; Umme Hani; Sowmya G Shivappa; Rashmi P Mahale; Anil Kumar; Ravindran Kumar (Journal of Krishna Institute of Medical Sciences University, 2023)
Background: Globally Hepatitis C Virus (HCV) is considered to cause one of the major infection burdening public health. Presently HCV is categorized into seven genotypes and 67 subtypes, transmitted through various routes and vary in their pathogenesis. Aims and Objectives: Present work aimed to detect the prevalent HCV genotypes among individuals attending tertiary care hospital. Material and Methods: A hospital based cross sectional study was carried out. Patient blood samples received for screening of HCV antibodies were included in this study. Serum was subjected to Enzyme-Linked Immunosorbent Assay (ELISA) or Chemiluminescent Immunoassay (CLIA) and samples found to be positive for HCV antibodies were subjected to viral RNA extraction and genotyping. Results: Forty-two samples were found to be positive for HCV antibodies out of 19526 samples screened and were further subjected to genotyping. The genotypes identified were genotype-1, genotype-3, and genotype-4. Conclusion: Genotype-1 and genotype-3 predominate in this region. However, genotype-4 detection was novel to this region and has never been reported earlier. This study highlights the importance of screening HCV-positive patients for genotyping.